Candida albicans in oral biofilms could prevent caries - Willems, Hubertine Marjoleine; Kos, Kevin; Jabra-Rizk, Mary Ann; Krom, Bastiaan P. (Pathogens and disease, 2016)
Streptococcus mutans is a Gram-positive bacterium involved in development to caries, the most common infectious disease of our time. Streptococcus mutans interacts with other microbes, like the fungus Candida albicans and both are commonly isolated from patients with caries. Since the role of C. albicans in caries remains unknown, our aim was to unravel this using an in vitro dual-species cariogenic oral biofilm model. Biofilms were grown for 24–72 h on glass cover slips or hydroxyapatite (HA) disks to mimic the surface of teeth. Medium pH, lactic acid production capacity and calcium release from HA disks were determined. All 24-h biofilms had external pH values below the critical pH of 5.5 where enamel dissolves. In contrast, 72-h dual-species biofilms had significantly higher pH (above the critical pH) and consequently decreased calcium release compared to single-species S. mutans biofilms. Counter intuitively, lactic acid production and growth of S. mutans were increased in 72-h dual-species biofilms. Candida albicans modulates the pH in dual-species biofilms to values above the critical pH where enamel dissolves. Our results suggest that C. albicans is not by definition a cariogenic microorganism; it could prevent caries by actively increasing pH preventing mineral loss. While Candida albicans is commonly isolated from patients with caries, it is not per se a cariogenic species; it could prevent caries eventually. Graphical Abstract Figure. While Candida albicans is commonly isolated from patients with caries, it is not per se a cariogenic species; it could prevent caries eventually.